Loss of Africanized honeybee (Apis mellifera) colonies with signs associated with the disease known as “Mal de Mayo” in Pérez Zeledón, San José, Costa Rica - Calderón-Fallas, Rafael A. (2025)
In Costa Rica, particularly in areas such as San Carlos and Pérez Zeledón, a honeybee disease known as “Mal de Mayo” has been reported, resulting in colony losses during April and May. This condition is characterized by larvae with a sac-like structure filled with liquid, exhibiting signs similar to those described for the Sacbrood viral disease. Using various tests, the presence of the virus was excluded, and the association was attributed to pollen from trees or plants in bloom at that time. This study was conducted in an apiary comprising 10 Africanized honeybee colonies in Pérez Zeledón, San José, during April and May 2024. Four colonies were selected, and a piece of honeycomb containing affected brood was collected. In the laboratory, uncapped brood was examined, and the larva was removed and placed in a petri dish for observation. In addition, the number of affected brood in each comb was estimated by counting the entire brood and calculating the proportion of affected brood. The type of pollen present in affected larvae and honeycombs was identified through palynological analysis. The presence of “Mal de Mayo” was recorded in most colonies starting April 11th. Upon examination of the combs on April 30th, 14.0% of larvae showed signs. As the disease progressed to severe levels (1.5 months later: May 26), 8 of 10 colonies were lost, and 1 was reduced to a nucleus. Furthermore, Varroa destructor mites and Nosema spp. microsporidia were present at low levels. Consequently, it can be inferred that “Mal de Mayo” disease caused considerable damage, since 80.0 % of the colonies exhibiting clinical signs were lost. The flowering period of the tree Vochysia ferruginea coincided with the onset, development, and conclusion of the disease.